Effect of environmental enrichment and composition of the social group on the behavior, welfare, and relative brain weight of growing rabbits - Bozicovich, Thais F.M. [UNESP] (2016)
The objective of the study was to investigate if environmental enrichment and the composition of the social group would affect the behavior and relative brain weight of growing rabbits. Rabbits (72 males and 72 females) were assigned to cages with or without enrichment and one of three social groups (males, females, or mixed-gender). Two eucalyptus sticks suspended from the cage ceiling were provided in the enriched cages based on the results of a preliminary trial conducted on growing rabbits (n = 48) showing that pieces of wood (Eucalyptus sp, Pinus sp) or bamboo (Dendrocalamus giganteus) were preferred over PVC pipe (P < 0.05). Rabbits were exposed to the experimental conditions between six and 11 weeks of age. Behavioral activities were video recorded for 24 h, at 7, 10 and 11 weeks of age. Growth performance was recorded from 42 to 77 days of age, whereas skin wounds and brain weight were recorded at 77 days. At 70 days of age, rabbits in non-enriched cages showed a higher proportion of self-grooming (P = 0.012) than those in enriched cages. Enrichment decreased the number of social interactions among rabbits (P = 0.012), but increased aggressive behavior (P = 0.007). The number of animals showing skin wounds on day 77 was lower (P = 0.006) in enriched than in non-enriched cages. The incidence of social interactions was higher (P < 0.05) and of stereotypes was lower (P < 0.05) in mixed-gender groups than in same-sex groups. Female groups showed the lowest incidence of aggressive behavior (P < 0.05). The number of individuals with skin injuries was higher in mixed-gender groups (P < 0.05) than in female groups; male groups were intermediate. Growth performance was unaffected by enrichment or by the composition of social group. Males in enriched cages had heavier brains (P < 0.05) than those in non-enriched cages. Although aggressive behaviors were more frequent, the number of skin wounds on day 77 was lower in rabbits from enriched cages, suggesting improved welfare. Based on the increased frequency of social interactions and decreased incidence of stereotyped behavior, mixed-gender groups should be housed in collective cages from weaning up to 11 weeks of age. However, if the incidence of skin wounds is considered, only females can be housed in same-sex groups. For males, individual cages should be preferred. Whether environmental enrichment induces morphologic changes in male rabbits’ brains should be further investigated.